The Relationship Between Tramadol-Induced Oxidative Testis Injury and Reproductive Function Disorder and Adenosine Triphosphate - Bedir, Fevzi; Kocatürk, Hüseyin; Altay, Mehmet Sefa; Mammadov, Renad; Süleyman, Bahadır; Coban, Taha Abdulkadir; Yazici, Gülce Naz; Bulut, Seval; Süleyman, Halis (Life (Basel, Switzerland), 2025)
Tramadol, a central analgesic drug, is used to treat moderate to severe pain but can cause reproductive disorders. The pathogenesis of tramadol-induced reproductive damage may involve increased oxidative stress, pro-inflammatory cytokines, ATP depletion, and reduced antioxidant levels. In this study, subjects were divided into four groups: healthy control (HC), tramadol only (TM), ATP only (ATP), and ATP + tramadol (ATM). ATP was administered intraperitoneally at 4 mg/kg, and tramadol was administered orally at 50 mg/kg. Distilled water was given to the HC group. This regimen was repeated for three weeks. At the end of the treatment, testicular tissues from six rats in each group were analyzed biochemically and histopathologically after euthanasia. The remaining rats’ reproductive functions were evaluated. Long-term tramadol exposure resulted in oxidative stress, inflammation in testicular tissue, and reduced male reproductive capacity. Thinning of seminiferous tubule walls and thickening of basement membrane, irregularity in germ cells, increase in interstitial connective tissue, congestion in vessels, increase in Leyding cells and hyperplasia were found in the TM group. ATP treatment significantly reduced tramadol-induced increases in oxidants and pro-inflammatory cytokines, reversed the decline in antioxidants, and mitigated infertility in testicular tissue. Furthermore, ATP preserved the morphology of the testicular tissue. These findings suggest that ATP may offer therapeutic potential for tramadol-induced infertility.